Los derechos y las meras expectativas: el ascenso de los agentes de control municipal - Quezada Riofrio, Jessica Abigail (2023)
This Degree Work, has been carried out taking into account the base Código Orgánico de Entidades de Seguridad Ciudadana y Orden Público legal, law that gave time for the GADS to develop the structural, functional, numerical, career plan, entry, training, promotions, evaluations and more regulations that have been necessary for the application of this regulation and that make possible the promotion of control agents municipal, in the Loja Canton, Ordinance 028-2021, has been published in the official registry on March 12th , 2021, a requirement has been added that the server must remain “6 years in the same degree of Operational Technician and 8 years in the managerial grade”, requirement that has broken what is stipulated in article 227 of the COESCOP, and this goes against the promotion system based on merit and competitive examination, In addition, after four years and nine months, the regulations for promotion and hierarchy in the (GAD) Municipio de Loja Although it is the same Constitución de la República del Ecuador , and the infra-constitutional norms, they have been aimed at achieving this objective, through the effective, legitimate, expeditious and due application of all those regulations in favor of the rights of the servants of the municipal control body. The GAD municipal del Cantón Loja has failed to comply with legal provisions and has ended up affecting the opportunity for promotion of municipal control servants.